Investment analysis - Prime, John H. (Englewood Cliffs, N.J. : Prentice-Hall, 1959)
This book is designed both for the student of investments and for the investor himself, to each of whom the fundamental principles underlying the theory and practice of investing are important. The book is divided into two parts: the name of investments, and the analysis of corporate financial statements.
Includes bibliographical footnotes and index.
rpm 24/01/2019
Loans
Keywords: Investment